Twitter Media Activities: Virtual Activism Related To China Uighur Muslim Problems - Buntoro, Kukuh; Suswanta, Suswanta; Nurmandi, Achmad; Setiawan, Anang; Saputra, Herdin Arie (Jurnal Tarbiyatuna, 2021)
Cases of human rights violations against Uighur Muslims in China have generated various condemnations from the international community. Various forms of protest, ranging from taking to the streets, complaints in mass media, and on social media. Several countries officially submitted objections to the Chinese government, including the superpower country of the United States. This research wants to see how the forms of protest in social media Twitter analyze the network patterns and relationships between the formed actors and the possibility of a new social movement. Through the hashtag feature on Twitter, researchers can analyze networks, messages, and protest delivery distribution using the Social Network Analysis (SNA) method. This study uses qualitative research methods, data collection by analyzing Twitter media activity, which is used as a protest to the Chinese government. The data was processed using NVivo 12 Plus software. The results showed that the relationship between actors in the use of social media Twitter has pressure on public opinion in parts of the world, the network pattern that connects countries in response to the issue of intimidation by the Uighur Muslim community, social protests that are always given by Twitter users as a place to pressure the Chinese government, and created a new social movement carried out by countries that support the resistance to intimidation by the Uighur people in Xinjiang.